OPTIMIZATION OF THE REPUBLIC OF INDONESIA’S OMBUDSMAN INSTITUTION AGAINST MALADMINISTRATION PUBLIC SERVICES VIEWED FROM ADJUDICATION THEORY PERSPECTIVE - Benny Akbar; Ellydar Chaidir; Efendi Ibnu Susilo (International Conference On Law And Social Sciences, 2024)
The government essentially plays a crucial role in providing public services to the community (public service). Therefore, the government is obliged and responsible to provide good and professional public services including regulations and various essential services such as health, utilities, education and administration. Public services are the main pillar in reflecting smooth governance and fulfilling people's rights in a fair and transparent manner. In Indonesia, the Ombudsman institution has a central role in responding to and supervising malmanagement, aiming to ensure that public services are carried out according to correct principles and in accordance with applicable legal norms. The problem, Why is the Ombudsman institution not optimal in handling public service maladministration from the perspective of adjudication theory, and What is the strategy for optimizing the Indonesian ombudsman institution in handling maladministration of public services seen from the perspective of Adjudication Theory. The research results show that even though they are not legally binding, the ombudsman's recommendations have a significant moral influence. Many public institutions have responded positively to the ombudsman's recommendations, however, there are still obstacles and challenges related to the lack of strong legal mechanisms to enforce compliance. So as to optimize and strengthen the role of the ombudsman institution and public understanding of its recommendations to increase integrity and effectiveness in improving the quality of public services